174k views
0 votes
If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f circle g) (x)? (3x + 2)(x 2 + 1) 3x 2 + 1 + 2 (3x + 2)2 + 1 3(x 2 + 1) + 2

User Sargupta
by
5.5k points

2 Answers

4 votes

Answer:

(f circle g) (x) = 3x^2 + 5

Explanation:

User Bobomoreno
by
6.3k points
3 votes

Answer:

(f circle g) (x) = 3x^2 + 5

Explanation:

To find (f circle g)(x), we substitute function g(x) for x in f(x) = 3x + 2:

(f circle g) (x) = 3(x^2 + 1) + 2, or

3x^2 + 3 + 2, or

(f circle g) (x) = 3x^2 + 5

User Epochwolf
by
5.4k points